Institutional changes in the process of national development : a case for the role and independence of central banks - Venner, K. Dwight (Caribbean Centre for Monetary Studies St. AugustineTT, 1997)
Presents an introduction to the institutional and policy parameters of decision making and implementation practices in the region. Looks at the rationale and experience of central bank independence. Analyses the Caribbean experience and sets out the options for the role of central banks in the development process.